Nasal Chondromesenchymal Hamartoma, a Rare Tumor in Young Children: A Case Report - Raad, Nasim; Ghorbani, Jahangir; Rekabi, Mahsa; Yousefi Koosha, Maryam; Karimi-Galougahi, Mahboobeh (Journal of Otorhinolaryngology and Facial Plastic Surgery, 2023)
Background: Nasal chondromesenchymal hamartoma (NCMH) is a very rare benign tumor of sinonasal tract with mixed components of predominantly mesenchymal and cartilaginous tissues which is mostly seen in infants and young children. Case presentation: We present the case of an infant with a nasal chondromesenchymal hamartoma which was confused with a malignancy. This clinicopathologic entity is notable because of its rarity and also it may present a diagnostic dilemma with major implications in management. Discussion: Nasal chondromesenchymal hamartomas (NCMHs) are rare, mostly benign lesions found in the nasal cavity and paranasal sinuses. They can be locally destructive and may be mistaken for malignant tumors due to their aggressive appearance. NCMHs consist of various lobulated mesenchymal components, with areas of fibro-osseous proliferation. They can cause nasal mass, obstruction, respiratory distress, maxillary bulge, or proptosis, and may extend to the adjacent paranasal sinuses. Radiological imaging is essential for differential diagnosis and evaluating surrounding tissues. Complete surgical excision is sufficient therapy for NCMHs. Conclusion: We present a rare case of NCMH, which can be difficult to distinguish from malignant tumors. Although NCMH are benign lesions, there is a chance of recurrence following incomplete resection. Recurrence may mimic malignancy, and their differentiation is important for choosing appropriate treatment.